Catalytic Pyrolysis of Corn Cob Using Fe-Ni/Char Catalyst - Safitri, Mutia; Azis, Muhammad Mufti; Wintoko, Joko; Kristanto, Jonas; Caroko, Novi (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
There is a growing interest to convert biomass waste such as corn cob to biofuel. Thermal conversion such as pyrolisis may play an important role to produce bio-oil. The objective of this research was to develop a kinetic study of catalytic pyrolysis of corn cob over Fe-Ni/Char catalyst using Thermogravimetric Analysis (TGA). The solid catalyst was prepared by impregnation method. The ratio of the percentages of Fe and Ni metals in the X-Ray Fluorescence (XRF) analysis of the catalyst was close to 1:1, resulting in metal loading values of 2.5% (1.062% and 1.013%), 5% (2.291% and 2.794%), and 10% (4.947% and 5.417%) for the catalyst. The pyrolysis experiments were performed using various catalyst loadings of 0, 2.5, 5, and 10%. In addition, the present study also investigated the influence of heating rates of 5, 10, and 20 K min-1. Two isoconversion models, Kissinger-Akahira-Sunose (KAS) and Ozawa-Flynn-Wall (OFW) were utilized to determine the activation energies. The activation energies calculated using the KAS and OFW models revealed a consistent trend, with values of activation energy of corn cob pyrolysis around 124 - 303 kJ/mol and 133 - 313 kJ/mol, respectively.